Pengaruh Model Problem Based Learning Terhadap Kreativitas dan Kolaborasi Siswa dalam Pembelajaran IPS di UPT SMPN 6 Tambang - Siska Deswita (Journal of Innovation in Teaching and Instructional Media, 2026)
This study aims to analyse the effect of the application of the Problem Based Learning (PBL) model on students’ creativity and collaboration ability in Social Science (IPS) learning at UPT SMPN 6 Tambang. The research uses a quantitative approach with a quasi-experimental research type and Pre-test–Post-test Control Group Design. The research subjects consisted of all 35 students in grade IX, which were divided into experimental classes and control classes through saturated sampling techniques. The experimental class was treated using the PBL model, while the control class used the conventional discussion method. Data collection was carried out through pre-test and post-test tests, creativity and collaboration ability questionnaires, and student activity observation sheets. Data were analysed using descriptive and inferential statistics with t-tests after meeting the prerequisite tests of normality and homogeneity. The results showed a significant difference between the experimental class and the control class, in which the application of the PBL model was proven to be more effective in increasing students’ creativity and collaboration skills. The novelty of this research lies in the integration of simultaneous measurement of creativity and collaboration in the context of social studies learning at the junior high school level with the PBL approach. The practical implications of this study suggest that the PBL model can be applied as an innovative learning strategy to support 21st century skills development. The contribution of this research is expected to be an empirical reference for teachers and curriculum developers in designing more active, collaborative, and meaningful social studies learning.